Role of Customer Relations Activities of PT.PLN (Persero) ULP Daya in Improving Business, Customer Satisfaction, and Assessing Service Quality Performance - Andi Mappatompo; Sri Mulyani Indrawaty; Agusdiwana Suarni (Jurnal Ilmu Manajemen Profitability, 2023)
The purpose of this research is to conduct a qualitative study aimed at understanding the role of PT. PLN (PERSERO) ULP DAYA in enhancing customer satisfaction and evaluating service quality performance. The sample for this study was collected from the PLN office located at Jl. Batara Bira No. 3, Pai, Kec. Biringkanaya, Makassar city. The research was conducted at PT. PLN (Persero) ULP DAYA, which serves as a benchmark for the performance of PT. PLN (Persero) ULP DAYA and involves direct interactions with customers beyond administrative aspects. The methodology employed by the author is qualitative, employing data collection techniques including interviews, observations, and literature review. The sampling technique used in this study was the snowball technique. Data analysis encompassed data reduction, data presentation, and drawing conclusions. The research findings indicate that PT. PLN (Persero) ULP DAYA demonstrates a comprehensive understanding of attitudes and benchmarks for superior service. The organization strives to uphold its commitment to consumers/customers by fostering strong customer relations. Despite encountering various challenges, the service performance delivered by PT. PLN (Persero) ULP DAYA is considered commendable and satisfying. However, the level of satisfaction bestowed upon customers has not reached its full potential and does not cover all service dimensions, which encompass reliability, responsiveness, empathy, assurance/guarantee, and physical appearance. This situation arises due to ongoing complaints and grievances voiced by customers themselves, primarily concerning the perceived incompetence and insufficient responsiveness of PT. PLN (Persero) ULP DAYA in addressing customer needs. This issue is notably related to service quality performance, particularly in terms of responsiveness and empathy.